Compulsory Liability Insurance of the Entity Conducting Medical Experiments – Polemical Remarks - Węgrzyn, Maria; Wieteska, Stanisław; Janiszewska, Magdalena (Obowiązkowe ubezpieczenie odpowiedzialności cywilnej podmiotu przeprowadzającego eksperymenty medyczne – uwagi polemiczne, 2023)
Conducting medical experiments by healthcare entities is highly necessary as it is only through such actions that we can confirm the effectiveness of new solutions, however carrying out medical experiments involves unique risks that must/should be subject to special protection. The aim of this article is to address the debatable elements contained in the Regulation of the Minister of Finance regarding the civil liability of entities conducting medical experiments. The raised concerns are intended to improve the quality of the adopted legal solutions to increase the safety of all entities and individuals participating in the process of conducting medical experiments.
Financial Sciences. Nauki o Finansach, 2023, vol. 28, no. 2, s. 21-35
Keywords: medical experiment insurance; coverage amount for medical experiment insurance; insurance company liability in medical experiments; damage settlement in medical experiments; ubezpieczenie eksperymentów medycznych; suma gwarancyjna dla ubezpieczeń w eksperymentach medycznych; odpowiedzialność gwarancyjna zakładu ubezpieczeń w eksperymentach medycznych; likwidacja szkody w eksperymentach medycznych